Social Capital and Farmers’ Income in Maize (Zea mays) Production - Ikawati Karim; Ariady Arsal; Palmarudi Mappigau; Rahim Darma; M. Fikri Akbar (Saburai International Journal of Social Sciences and Development, 2018)
Social capital is an investment to get new resources in society. Weak social capital will dim the spirit of mutual cooperation, exacerbate poverty, increase unemployment, crime, and hinder any effort in improving the welfare of the population including farmers. Utilizing the potential of social capital had been able to contribute to improving income of farmers in the rural area. So that, it is important to analyze the significance of influence in social capital and farmers’ income of maize production in Jeneponto, South Sulawesi. Data were collected by structured interview through probability proportional to 120 of maize farmers as samples which were analyzed by descriptive analysis. Final resulted showed that Social capital through the dimensions of trust, social network and norms had a positive effect on farmers' income, but the effect was not significant.  The dimensions of social capital owned by new farmers formed a positive attitude that supported and had not directly influenced the increase in farmers' income, especially the increase in production as the highest dimension of income generation.